Pharmaceutical study & preliminary analysis of Sheetala Parpati - Chandra, Namitha R.; Karjagi, Satish P.; Hussain, Gazala (Journal of Drug Delivery and Therapeutics, 2019)
The Parpati kalpana is a thin flake form of mercurial preparation which is unique in the field of Rasashastra. It is one among the Chaturvidha Rasayana and Agnisthayi Murchita Parada Bandha i.e., Pota Bandha of Parada. Sheetala parpati is an Ayurvedic medicine that comes under Parpati kalpana, used in the treatment of difficulty in urination, urinary calculi, dyspepsia, etc. There are two different references of Sheetala Parpati where the ingredients and method of preparation are different. In the present work an attempt has been made to prepare both the varieties of Sheetala parpati along with its analytical study. It is mainly indicated in Mutrakricchra (Dysurea) and other diseases like Amlapitta (Hyperacidity), Udarashoola (Abdominal pain), Ajeerna (Indigestion), Yakritvikara (Hepatic disorder), etc. Keywords: Parpati kalpana, Chaturvidha Rasayana, Sheetala Parpati, Mutrakricchra (Dysurea)